MUSYAWARAH PERENCANAAN PEMBANGUNAN (MUSRENBANG) DI KEPENGHULUAN SUNGAI SEGAJAH JAYA KECAMATAN KUBU KABUPATEN ROKAN HILIR TAHUN 2015 - ", Nurmala; Rusli SD, Zaili (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The village is the Musrenbang planning forum (program) is implemented by public institutions, namely the village government, in cooperation with citizens and other stakeholders. Musrenbangdes in Kepenghuluan Segajah River Jaya still minimal and still passive, it is due to a lack of understanding on development planning, low levels of education, and lack of socialization and lack of public participation in the government apparatus Kepenghuluan.The concept of the theory used in this research is sanders Communication by explaining that in analyzing the development of society, we can see the communication from the four perspectives, namely Process, Method, Program and social movements. This study aims to find out about the Development Planning Meeting (MUSRENBANG) in Kepenghuluan Segajah Jaya Sungai Kubu Rokan Hilir District of the Year 2015. This research uses qualitative research methods and assessment of descriptive data. In this collection of data collection using interview techniques, observation, and documentation. By using the informant as a source of information.The results showed that the implementation of development planning Kepenghuluan Segajah Jaya Sungai not optimal and maximum efficiency and effective action has not been done so that the results are not based on the needs of the community, so there are still a lot of development needs of the community but is not included in the proposal development and planning'm absolutely not felt the benefits and impacts positively by the public.This study suggests that the government Kepenghuluan order to improve the quality nor the capacity of human resources in the implementation and administration Musrenbangdes Kepenghuluan should take decisions and policy development programs based on community needs and development of the most prioritized so that no misunderstanding to a predefined program.Keywords: Consultation, planning, development